n-Hexane Extract of Mangrove Leaves Effect on p21 and Akt 2 Gene Expressions of WiDr Cells - A, Istiqomah M; Z, Hasibuan P. A.; M, Basyuni (Asian Journal of Pharmaceutical Research and Development, 2019)
Objectives: The study aims to examine the anticancer effect of polyisoprenoid of Nypa fruticans, Ceriops tagal, and Rhizophora mucronata leaves in WiDr cells by evaluating the regulation of p21 and Akt 2 gene. Design: Nypa fruticans, Ceriops tagal, and Rhizophora mucronata leaves were dried and extracted with n-hexane, analyzed the increase or decrease in regulation of p21 gene and Akt 2 expression which was determined the Reverse Transcription Polymerase Chain Reaction (RT-PCR) method. Interventions: The variable that was intervened in this study was the 3 sample mangrove leaves. Main outcome measure: The main measurement results in this study were to study n-hexane extracts of mangrove leaves able to suppress the expression of p21 and Akt 2 genes so that cancer cell growth is inhibited. Results: n-hexane extract of Ceriops tagal leaves was more effective than Nypa fruticans and Rhizophora mucronata, in which there was up-regulated (p21) of 1.19 and down regulated (Akt 2) of 0.78 on colon cancer cells (WiDr). N-hexane extract of mangrove leaves has cancer chemoprevention activity with up-regulated and down-regulated on WiDr cells, in which the sample was more effective than n-hexane extract of Ceriops tagal leaves. Conclusion: N-hexane extract of mangrove leaves had cancer chemoprevention activity with up-regulated and down-regulated on WiDr cells, in which the sample was more effective than n-hexane extract of Ceriops tagal leaves.